Structure and photoluminescence of di-amidosil nanohybrids incorporating europium triflate - Nunes, Sílvia (2008)
The sol–gel process was used to prepare amorphous di-amide cross-linked alkyl/siloxane hybrid materials (di-amidosils) incorporating europium triflate (Eu(CF3SO3)3). Samples with 200 ≤ n ≤ 8 (where n is the molar ratio of carbonyl oxygen atoms per Eu3+ ion) were studied. The conformations of the alkyl chains of the host matrix in the doped di-amidosils (essentially gauche) are not affected by the presence of the salt. The Eu3+ ions bond to the C=O groups of the amide cross-links in the whole range of salt concentration examined. “Free” and weakly coordinated triflate ions were detected in all the samples analyzed. At n = 8 an ionic aggregate of unknown nature is formed. The hybrids introduced are room temperature white light emitters due to the convolution of the hybrid host emitting centers (amide cross-linkages and siliceous nanodomais) and the Eu3+ intra-4f6 5D0 → 7F0–4 transitions. Photoluminescence data suggest that in the dilute di-amidosil with n = 100 the Eu3+ ions occupy the same type of chemical local environment.